2010
DOI: 10.2119/molmed.2010.00017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Eight Novel SMPD1 Mutations Causing Types A and B Niemann-Pick Disease

Abstract: Types A and B Niemann-Pick disease (NPD) result from the deficient activity of acid sphingomyelinase (ASM), due to mutations in the sphingomyelin phosphodiesterase 1 (SMPD1) gene. Here we report the identification, characterization and genotype/phenotype correlations of eight novel mutations in six unrelated NPD patients. These mutations included seven missense mutations: c

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 10 publications
(13 reference statements)
1
26
0
Order By: Relevance
“…This mutation in RsASML corresponds to the H427R mutation in human aSMase found in a subset of Niemann-Pick Type A patients [37]. RsASML H280R did not display any activity towards pNPPC (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…This mutation in RsASML corresponds to the H427R mutation in human aSMase found in a subset of Niemann-Pick Type A patients [37]. RsASML H280R did not display any activity towards pNPPC (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…In patient 15, both p.Ser250Arg and p.Glu471Lys mutations were of maternal inheritance. Previously, the p.Ser250Arg mutation has been reported in combination with a premature stop codon, in a Dutch patient with a mild form of type A NPD [10]. In this study, we were unable to determine the pathogenicity of p.Glu471Leu.…”
Section: Resultsmentioning
confidence: 70%
“…Another variation, p.Ala541Thr, was identified on the same allele as p.Pro533Leu, in patient 4. To fully understand the complete effects of these three variations, expression studies need to be conducted as previously reported [10]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations